Risk indicators for peri‐implant mucositis: a systematic literature review. (April 2015) - Renvert, Stefan; Polyzois, Ioannis
Abstract: Objectives: To examine the existing evidence in identifying risk indicators in the aetiology of peri‐implant mucositis. Material and Methods: A search was performed in PubMed, Web of Science (WOS) and The Cochrane Library databases for articles published until June 2014. Results: This search gave 3135 results of which 15 studies fulfilled the inclusion criteria. The current review revealed that only a few studies provided data on risk indicators for the development of peri‐implant mucositis. Based on the data available, there is evidence that plaque is a risk indicator for peri‐implant mucositis. Smoking has also been identified as an independent risk indicator whereas the overall evidence for surface roughness, residual cement, the dimension of the keratinized tissue and time of implant in function is weak. There are limited data available to support systemic conditions as risk indicators for peri‐implant mucositis. Conclusions: Plaque accumulation at implants will result in development of peri‐implant mucositis. Smoking should also be considered as a risk indicator for the development of peri‐implant mucositis.